Fatal Poisonings: Autopsy-Based Study - Gurger, Mehtap; Vicdanli, Nazif Harun; Turkoglu, Abdurrahim; Bork, Turgay; Gocuk, Vahap; Goktekin, Mehmet Cagri; Gul, Evrim (Galenos Publ House, 2023)
Objective: Poisoning is an important public health problem. This study aimed to investigate the demographic characteristics, toxic agents causing death, and the cause of exposure in victims who died due to poisoning. Methods: In this autopsy-based retrospective study, the demographic data, exposure to toxic substances, cause of death, and date and place of death of victims who died due to poisoning between January 2011 and December 2020 were recorded. Results: A total of 90 fatal poisoning cases were investigated. The majority of the victims were male (n=69, 76.7%) with a mean age of 43.2 +/- 21.5 years. While 13 (14.4%) patients were younger than 18 years old, 14 (15.6%) were 65 years or older. The majority of deaths occurred at the scene (54.4%) and during the winter season (37.8%). While accidental exposure (41.1%) was the most common cause, suicide (31.1%) was the second. Carbon monoxide (CO) was the main toxic agent causing death, followed by the use of prescription drugs and illicit drugs. Conclusion: CO is the most common cause of death, and the vast majority of victims were exposed by accident. It is important to educate the public and take the necessary precautions in reducing these deaths. Prescription drugs and illicit drugs were other common causes of death, respectively.
Keywords: Fatal; poisoning; autopsy